Determinants of chronic energy deficiency (CED) in pregnant women in stunting - Irma, Irma; Rahman, Sugirah Nour; Ryska, Hasra; Hadju, Veny (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Chronic Energy Deficiency (CED) in pregnant women is a condition resulting from prolonged malnutrition, particularly insufficient energy and protein intake. This condition significantly increases the risk of maternal and infant mortality, low birth weight (LBW), and contributes to stunting in children. This study aims to identify the determinants influencing the incidence of CED among pregnant women in the stunting. Method: A cross-sectional observational study was conducted among 201 pregnant women selected through purposive sampling from 30 stunting-prone villages. Data collection involved Android-based questionnaires and anthropometric measurements using Mid-Upper Arm Circumference (MUAC). Statistical analyses included chi-square tests for bivariate analysis and logistic regression for multivariate analysis. Results: The prevalence of CED among the participants was 15.9%. Significant factors associated with CED included maternal age (p=0.000; OR=2.79; 95% CI: 1.67–4.64), employment status (p=0.016; OR=6.73; 95% CI: 1.58–27.94), antenatal care visits (p=0.004; OR=11.31; 95% CI: 2.71–28.19), pregnancy spacing (p=0.023; OR=6.80; 95% CI: 1.31–26.8), family smoking history (p=0.002; OR=0.45; 95% CI: 0.27–0.75), and family income (p=0.013; OR=5.24; 95% CI: 1.73–26.02). Conclusion: CED among pregnant women is significantly influenced by age, occupational status, antenatal care frequency, pregnancy interval, family exposure to cigarette smoke, and low household income. Strengthening antenatal care services, promoting family planning, enhancing nutrition education, and mitigating environmental risk factors such as secondhand smoke exposure are essential strategies to reduce CED and its adverse health outcomes.